DYNLL1 binds to MRE11 to limit DNA end resection in BRCA1-deficient cells. (22nd November 2018) - He, Yizhou; Meghani, Khyati; Caron, Marie-Christine; Yang, Chunyu; Ronato, Daryl; Bian, Jie; Sharma, Anchal; Moore, Jessica; Niraj, Joshi; Detappe, Alexandre; Doench, John; Legube, Gaelle; et al.
Abstract Limited DNA end resection is the key to impaired homologous recombination inBRCA1 -mutant cancer cells. Here, using a loss-of-function CRISPR screen, we identify DYNLL1 as an inhibitor of DNA end resection. The loss of DYNLL1 enables DNA end resection and restores homologous recombination inBRCA1 -mutant cells, thereby inducing resistance to platinum drugs and inhibitors of poly(ADP-ribose) polymerase. Low BRCA1 expression correlates with increased chromosomal aberrations in primary ovarian carcinomas, and the junction sequences of somatic structural variants indicate diminished homologous recombination. Concurrent decreases in DYNLL1 expression in carcinomas with low BRCA1 expression reduced genomic alterations and increased homology at lesions. In cells, DYNLL1 limits nucleolytic degradation of DNA ends by associating with the DNA end-resection machinery (MRN complex, BLM helicase and DNA2 endonuclease). In vitro, DYNLL1 binds directly to MRE11 to limit its end-resection activity. Therefore, we infer that DYNLL1 is an important anti-resection factor that influences genomic stability and responses to DNA-damaging chemotherapy. DYNLL1 antagonizes end resection of DNA double-strand breaks, thereby inhibiting homologous repair, and the loss of DYNLL1 correlates with poor progression-free survival of patients withBRCA1 -mutant ovarian cancer.